1993
DOI: 10.1016/s0006-3495(93)81205-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy-minimized structures and packing states of a homologous series of mixed-chain phosphatidylcholines: a molecular mechanics study on the diglyceride moieties

Abstract: Phosphatidylcholines or C(X):C(Y)PC, quantitatively the most abundant lipids in animal cell membranes, are structurally composed of two parts: a headgroup and a diglyceride. The diglyceride moiety consists of the glycerol backbone and two acyl chains. It is the wide diversity of the acyl chains, or the large variations in X and Y in C(X):C(Y)PC, that makes the family of phosphatidylcholines an extremely complex mixture of different molecular species. Since most of the physical properties of phospholipids with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…According to the authors, a ratio ranging from 0.44-0.57 is typical of mixed interdigitated gel phases (56), although Lewis et al (40) showed that some PCs whose DC/CL ratios were not in the defined range were able to form mixed interdigitated gel phases (40). For NCer, DC/CL ¼ 0.41, i.e., a value consistent with a change from a partial interdigitated to a mixed interdigitated gel phase (57).…”
Section: Thermotropic Behavior Of Ncer and Properties Of Phasesmentioning
confidence: 99%
“…According to the authors, a ratio ranging from 0.44-0.57 is typical of mixed interdigitated gel phases (56), although Lewis et al (40) showed that some PCs whose DC/CL ratios were not in the defined range were able to form mixed interdigitated gel phases (40). For NCer, DC/CL ¼ 0.41, i.e., a value consistent with a change from a partial interdigitated to a mixed interdigitated gel phase (57).…”
Section: Thermotropic Behavior Of Ncer and Properties Of Phasesmentioning
confidence: 99%
“…Molecular mechanics (MM) calculations, which include the model building of the energy-minimized structures of monomeric lipid and higher lipid aggregates in the absence of H20, or in vacuo, and the generation of the overall steric energy associated with each of the energy-minimized structures, were carried out using Allinger's MM2 (85) program (Allinger, 1977), as described previously (Li et al, 1993). These MM calculations were performed on an IBM RS/6000 computer and Silicon Graphics/ Indigo2 workstations.…”
Section: Molecular Mechanics Calculationsmentioning
confidence: 99%
“…The letter 0 is used to designate the oxygen atom of one lipid's carbonyl group on the sn-I acyl chain as well as the oxygen atom of the hydroxyl group of an ethanol. C(X):C(Y)PCs were modeled similarly in vacuo, based on crystal coordinates of the same modified DMPC molecule using the procedure described earlier (Li et al, 1993;Huang and Li, 1996). The AC values, however, were distinctly different for different molecular species of C(X):C(Y)PC.…”
Section: Packing Models For Aggregated Anhydrous Phosphatidylcholinesmentioning
confidence: 99%
See 2 more Smart Citations